An optimized sheet metal forming process using non-isothermal heating system - Tan, Ming-Jen (2013)
The process parameters used in the hybrid superplastic forming have been optimized. Since the hybrid process was a combination of hot drawing and gas blow forming, the effects related with the two forming phases were taken into account to facilitate the process design. The punch shape has been modified. A two-stepped punch in accordance with the die geometry with length of 43 mm was used in this work. Finite element modeling (FEM) was carried out to detect the low-plastic-strain areas, where the materials would have capabilities to be deformed more as the temperature increased. The non-isothermal heating system was then adopted to heat up these selected areas to improve the material formability during deformation. The maximum thickness thinning of the formed sample was 40%. Microstructures observed via electron backscattered diffraction (EBSD) have shown the occurrence of grain growth and recrystallization. It is clear that no big structure defect resulting from large plastic deformation was found.